Birthweight specific trends in cerebral palsy. Issue 6 (June 1990) - Pharoah, P O; Cooke, T; Cooke, R W; Rosenbloom, L
Abstract : A register of infants with cerebral palsy born to mothers resident in the Mersey region from 1967-84 has been maintained using various sources of information. A total of 1056 patients are registered of whom 331 (31%) have hemiplegia or mixed hemiplegia, 236 (22%) have diplegias or mixed diplegia, and 369 (35%) have quadriplegia or mixed quadriplegia. The remainder have dyskinetic or dystonic forms except for seven, who are unclassified. There has been no significant change in the prevalence of cerebral palsy among infants of normal birth weight (greater than 2500 g). Among low birthweight infants (less than or equal to 2500 g) there has been a significant increase in prevalence of all the main clinical types. This increase started later among the very low birthweight infants (less than or equal to 1500 g) than among those weighing 1501-2500 g. These changes in prevalence could be the result of either improved survival of prenatally impaired infants because of improvements in medical care, or a reflection of failure to maintain optimal conditions at or around the time of birth.